Pengembangan Profesionalisme Guru PAI di Era Digital: Studi Kepustakaan Tentang Integrasi Teknologi dalam Meningkatkan Kualitas Pembelajaran - Alvyatu Zaahra; Vevi Putri; Agus Joko Purwanto (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to review the integration of technology in Islamic education learning from a theoretical perspective using a descriptive qualitative library research method. The researcher collected and analyzed data from various written sources, including books, journal articles, research reports, and educational policy documents relevant to the research theme. The data collection technique in this study was carried out using document study techniques. The results of the study show that the use of technology, such as learning applications, e-learning platforms, virtual reality (VR), and augmented reality (AR), can increase the effectiveness of learning, expand the accessibility of teaching materials, and facilitate teachers in improving their skills in using technology. However, the application of technology also faces challenges, including infrastructure limitations, the readiness of educators and structures, and a lack of institutional support from both the government and the education sector. Thus, this study concludes that the integration of technology in Islamic education has great potential to improve the quality of learning, provided that it is implemented with careful planning and adequate support.